LANGUAGE AND ITS RELATIONSHIP TO RELIGIOSITY - Sufrin Efendi Lubis (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2023)
Language serves as a means of communication among humans. Through language, individuals express their preferences and dislikes, as well as offer praise or criticism to others. This highlights the significant role language plays in a person's life, as it can bring respect or subject them to insult. Accordingly, there is an intrinsic relationship between language—particularly spoken language—and religiosity. This research aims to explore spoken language specifically, as the researcher will focus extensively on how individuals use speech to convey their intentions. The central research question is: "Is there a relationship between spoken language and the quality of religiosity?" This study employs a library research method, utilizing books as primary sources, supplemented by scientific articles, online publications, and other materials as needed. The findings reveal a reciprocal relationship between language and religiosity: language serves as the cause, and religiosity as the effect. The better one’s language, the stronger their religiosity appears; however, language alone is not the sole indicator of religiosity. It is possible for someone to speak gently and use kind words, yet still be cursed by Allah for hypocrisy and envy.